Treatment of COVID-19 Patients during Second Wave in a Tertiary Care Center of Nepal - Devkota, Pragya; Bajracharya, Omi; Manandhar, Tejendra; Kafle, Sajala; Jha, Nisha; Kafle, Kumud K; Sijapati, Milesh J (Journal of Institute of Medicine Nepal, 2022)
Introduction: The second wave of the COVID-19 pandemic was confirmed in Nepal in April 2021. It was caused by genetic variants of SARS-CoV2. The objective of the study was to find out severity of patients, their treatment and approximate drug cost for the treatment of COVID-19 in the second wave. Methods: In this retrospective, cross-sectional study, data of all patients who tested positive and were admitted in KIST Medical College and Teaching Hospital between April 2021 – July 2021 was collected for the study. A total of 215 patients were included. Results: Among the cases admitted, 190 (88.4%) patients were symptomatic. ICU/HDU admission was done in 113 (52.5%) cases, among which 33 (29.2%) patients received ventilator support. The patients treated in isolation unit were 102 (47.4%). Among the patients admitted, 23 (10.7%) were vaccinated. Severe cases were 80 (37%), moderate cases were 71 (33%) and mild cases were 49 (23%). Antibiotics were used in 190 (88.4%) cases. More than one antibiotics were used in 141 (65.6%) cases. Antifungals were used in 39 (18.1%) cases. Other drugs like corticosteroids were used in 185 (86%), proton- pump inhibitors in 179 (84.3%), antihistaminics in 169 (78.4%) and anticoagulants in 165 (76.7%), Vitamin C in 153 (71.2%), Vitamin D in 152 (70.7%) and zinc in 140 (65.1%) cases. The number of patients discharged after recovery was 151 (70.2%) and 41 (19.5%) patients died. The average drug cost was NPR. 3,246 in mild, 27,645 in moderate and 76,420 in severe cases. Conclusion: Majority of patients were treated in ICU/HDU. Most commonly used drugs were antibiotics, corticosteroids and anticoagulants. Mortality was high in the second wave.